Total Synthesis of Natural Products with Antimicrobial Activity - Giltrap, Andrew; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This thesis focuses on the development of efficient and scalable total syntheses of natural products that can be used as preferred scaffolds for anti-infective drug discovery. It describes the total synthesis of two classes of antimicrobial non-ribosomal peptides (NRPs) - teixobactin and the skyllamycins - with subsequent biological evaluation. The first part describes the first total synthesis of teixobactin by means of a solid-phase peptide synthesis-macrolactamisation approach, yielding a synthetic natural product that can combat a number of clinically relevant Gram-positive bacterial pathogens. The second part describes the first total synthesis of skyllamycins A-C, a family of structurally complex cyclic NRPs, which inhibit the growth of the Pseudomonas aeruginosa biofilms that are responsible for significant mortality among cystic fibrosis patients.
Introduction -- Total Synthesis of Teixobactin -- Synthesis of Deshydroxy Skyllamycins A-C -- Total Synthesis of Skyllamycins A-C -- Experimental.
Keywords: Medicinal chemistry; Clinical biochemistry; Medical microbiology; Medicinal Chemistry; Medical Biochemistry; Medical Microbiology